Real-time Marketing in Marketing Strategy of Barilla - Księcikowska, Magdalena (Linguistic creativity in marketing, 2022)
The article discusses the country-of-origin marketing strategy of an Italian food company Barilla in the field of using real-time marketing in its social media advertising campaigns. The paper presents the main purpose and principal functions of this marketing tool and provides the analysis of visual and verbal aspects of the posts published in the company's social media pages (including the form, subject matter and linguistic aspects of the slogans contained in the promotional graphics).